Bringing Technology to Students’ Proximity: A Sociocultural Account of Technology-Based Learning Projects - Mukama, Evode (International Journal for Research in Vocational Education and Training, 2014)
This paper depicts a study carried out in Rwanda concerning university students who participated in a contest to produce short documentary films. The purpose of this research is to conceptualize these kinds of technology-based learning projects (TBLPs) through a sociocultural perspective. The methodology included focus-group discussions and field notes to collect empirical data. The findings reveal that the more educational technologies capture objects of learning positioned in the students’ sociocultural proximity, the more focused the learners’ attention is on these objects. The study shows also that a change in learning projects may depend to a large extent on whether the technology relates to the students’ sociocultural proximity, that is, taking into consideration students’ physical, cultural, and contextual real world. The study recommends a community of learning/inquiry embedded in a collaborative, problem-solving dynamic involving cognitive support from peers, teachers, external specialists, and the wider community.